The Determinants of Success in the Implementation of Information Technology in Moroccan Companies: Exploratory Case Study - Alami, Mohamed (European Scientific Journal, ESJ, 2024)
The study, which is being conducted in the context of the widespread use of information technology in Moroccan companies, focuses on examining the success factors of IT implementation. This is a crucial step in maximizing the value of information technology investments. The goal is to address concerns regarding the delay in digital transformation and the role of information technology in establishing a sustainable and irreplaceable competitive advantage. The research methodology utilizes a qualitative approach, specifically a single case study with semi-structured interviews for data collection. The theoretical framework incorporates the resource-based view (RBV) and contingency theories. The key findings of the study emphasize the challenges encountered during information technology implementation, especially concerning the complementarity of organizational and human resources with information technology resources. Based on these challenges, the factors contributing to successful information technology implementation are categorized into three groups: pre-implementation phase, alignment of information technology strategy, and collaboration and coordination among all stakeholders involved in the implementation process.